Sociolinguistic Competence in Teaching Foreign Languages (Eurasian Journal of Learning and Academic Teaching, 2023)
The importance of considering sociolinguistic factors in the process and methodology of teaching a foreign language has become one of the main requirements in developing and improving the foreign language competence of students of non-linguistic universities. This can be due to the need for students to be capable of using language not only linguistically appropriate but also socially pertinent. As the focus is on the development of the sociolinguistic competence of future specialists, there is a need to select and incorporate relevant approaches to reinforce students’ professionally-oriented sociolinguistic competence. Reflecting on the CEFR “can-do” statements targeted to stimulate students to act in real-life situations, the paper emphasizes the importance of sociolinguistically-oriented teaching in non-linguistic universities. Also, the article highlights the approaches and the sort of activities teachers can use to facilitate students’ learning and development of professionally-oriented sociolinguistic competence. It is highly recommended to create a learning process where students can take an active part by participating in various authentic, hands-on, or student-led activities that can promote the student-centered sociolinguistically-oriented model of teaching